The relationship between extraversion and physical attractiveness of online network users assessed by personnel recruiters. (12th April 2016) - Shchebetenko, Sergei; Bergfeld, Alexandra Y.
Abstract: Objective: The objective of the study was threefold. First, we examined whether extraversion contributes to the evaluations of an online social network user's physical attractiveness made by professional recruiters. We studied if this relationship is mediated by a degree of user's activity and popularity among other users. Second, we presumed this relationship to be specified in terms of the five‐factor theory of personality. A type of characteristic adaptation named reflected extraversion was assumed to incrementally contribute to this relationship. Reflected extraversion is a meta‐perception representing one's opinion on how extraverted one is as perceived by significant others. Third, user popularity treated as an external influence in terms of the five‐factor theory was presumed to reciprocally affect reflected extraversion. Method: Profiles of 188 online social network users were assessed by four professional recruiters. The latter were asked to evaluate the physical attractiveness of the former. The users completed a number of self‐report measures. Various behavioural indicators extracted from the profiles were measured. Results: Extraversion enhanced recruiter‐rated physical attractiveness via two paths: user activity and user popularity. The inclusion of reflected extraversion failed to improve the model substantially. However, reflected extraversion mediated the link between trait extraversion and the indicators of user popularity but not the indicators of user activity. The reciprocal path from user popularity towards reflected extraversion was negligible. Conclusions: The study shows that extraversion may allow people to efficiently manage online networking to convince recruiters that they are physically attractive, even in the absence of any offline communications.